The effect of dietary interventions on inflammatory biomarkers among people with multiple sclerosis: A protocol for systematic review and meta-analysis of randomized controlled trials. - Farnoosh Shemirani; Wade R Pingel; Tyler J Titcomb; Asma Salari-Moghaddam; Farshad Arsalandeh; Solange M Saxby; Linda G Snetselaar; Terry L Wahls (PLoS ONE, 2024)
Background Multiple sclerosis (MS) is a chronic neuroinflammatory disease of the central nervous system, characterized by demyelination and neurodegeneration, which has a profound impact on the quality of life. Dysregulated inflammatory processes are a major driver of MS progression, with many areas of research being dedicated to modulating inflammation in people with MS. Several dietary patterns have been associated with improvements in inflammatory biomarkers; although, the findings have been inconsistent. Thus, this study aims to evaluate the effects of dietary interventions on inflammatory markers in adults with MS. Methods Electronic databases, including PubMed/MEDLINE, Web of Science, Scopus, and Cochrane/Central, will be searched. Screening, selection, and extraction of data, along with quality assessment of included studies, will be done by two separate reviewers, and any potential conflicts will be settled through discussion. Two reviewers will independently assess the risk of bias in included studies using the Cochrane Risk of Bias Tool. If plausible, the results will be synthesized and pooled for meta-analysis. The overall quality of evidence of each study will be evaluated using the NutriGRADE tool, which is a modification to the Grading Recommendations Assessment, Development, and Evaluation (GRADE) developed specifically for nutrition research. Discussion Studies have demonstrated conflicting results regarding the effects of dietary interventions on serum levels of inflammatory biomarkers among people with MS. Thus, it is expected that the planned systematic review and meta-analysis will yield robust evidence on the effects of diet on inflammatory profile in the setting of MS.